2020
DOI: 10.2147/dmso.s242431
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Factors Affecting the Severity of Diabetic Foot Ulcer in Patients with Diabetes Referred to a Diabetes Centre in Kermanshah</p>

Abstract: Introduction: Diabetes mellitus is a metabolic disease characterized by high blood sugar (BS) levels and the change in the metabolism of lipids, carbohydrates, and insulin resistance, and is one of the main causes of disability and mortality worldwide. Among the different types of complications, which have many negative effects on personal and social life, diabetic foot ulcer (DFU) is very important. This study aims to investigate the factors affecting the severity of DFU among patients with diabetes. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
5
0
2
Order By: Relevance
“…33 Also, in Ghobadi et al's study, cardiovascular complications showed more in DFU patients. 34 Brennan et al stated that ulcer severity is a more significant predictor of subsequent mortality than other complications. 18 Coagulase-negative Staphylococcusbacteria isolated from DFU were correlated with severity of DFU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Also, in Ghobadi et al's study, cardiovascular complications showed more in DFU patients. 34 Brennan et al stated that ulcer severity is a more significant predictor of subsequent mortality than other complications. 18 Coagulase-negative Staphylococcusbacteria isolated from DFU were correlated with severity of DFU.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not known precisely which complication of diabetes has more effect, it appears that the effect of microvascular complications is more than others in the severity of DFU. 33,34 Inadequate vascular status was another factor in DFU severity. 35 High BS, FBS and BS 2 hours after breakfast have been reported as other effective factors (P<0.05, P=0.026, P=0.016).…”
Section: Overview Of Factors Influencing Severity Of Dfumentioning
confidence: 99%
“…WHO (2018) menjelaskan bahwa kualitas hidup merupakan persepsi individu yang dikaitkan dengan tujuan, harapan, dan minat terhadap dirinya sendiri. UKD juga berdampak pada ekonomi keluarga dan sistem kesehatan, karena biaya perawatan yang mahal, selain itu juga dapat menyebabkan gangguan fisik dan emosi, sehingga dapat memperburuk kualitas hidup (Ghobadi et al, 2020). Hal ini sesuai dengan penelitian Alosaimi dkk., (2019); Khunkaew, Fernandez, (2019); Wukich, Raspovic, (2018); Siersma et al, (2017), yang melaporkan bahwa pasien UKD mempunyai kualitas hidup yang buruk.…”
Section: Pendahuluanunclassified
“…In relation to the behavior of early detection of diabetic foot in type 2 DM patients, a person will take health actions such as early detection if he has confidence in vulnerability, seriousness of a disease, benefits, obstacles in taking action and taking into account self-effica- cy or self-confidence in carrying out an action plus the existence of cues to action (cues to action) both from within and or outside the individual. 6,7 Nowadays, technological advances have developed rapidly, accompanied by the increasing use of the internet and smartphones as a means of communication in everyday life. In addition, the current use of smartphones is mainly based on Android, which is also used as a means of accessing health information in the form of telemedicine or telenursing.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to the behavior of early detection of diabetic foot in type 2 DM patients, a person will take health actions such as early detection if he has confidence in vulnerability, seriousness of a disease, benefits, obstacles in taking action and taking into account self-efficacy or self-confidence in carrying out an action plus the existence of cues to action (cues to action) both from within and or outside the individual. 6,7…”
Section: Introductionmentioning
confidence: 99%